JANUS: an open-source 3D printable perfusion bioreactor and numerical model-based design strategy for tissue engineering - Meneses, João; Fernandes, Sofia R.; Silva, João C.; Ferreira, Frederico Castelo; Alves, Nuno; Pascoal-Faria, Paula (Frontiers in Bioengineering and Biotechnology, 2023)
Bioreactors have been employed in tissue engineering to sustain longer and larger cell cultures, managing nutrient transfer and waste removal. Multiple designs have been developed, integrating sensor and stimulation technologies to improve cellular responses, such as proliferation and differentiation. The variability in bioreactor design, stimulation protocols, and cell culture conditions hampered comparison and replicability, possibly hiding biological evidence. This work proposes an open-source 3D printable design for a perfusion bioreactor and a numerical model-driven protocol development strategy for improved cell culture control. This bioreactor can simultaneously deliver capacitive-coupled electric field and fluid-induced shear stress stimulation, both stimulation systems were validated experimentally and in agreement with numerical predictions. A preliminary in vitro validation confirmed the suitability of the developed bioreactor to sustain viable cell cultures. The outputs from this strategy, physical and virtual, are openly available and can be used to improve comparison, replicability, and control in tissue engineering applications.